Partnerships in nursing homes: How do family caregivers of residents with dementia perceive collaboration with staff? - L Hoek; Jolanda CM van Haastregt; Erica de Vries; Ramona Backhaus; Jan P.H. Hamers; Hilde Verbeek (2020)
Background Partnerships between family and nursing staff in nursing homes are essential to address residents’ needs and wishes. Collaboration is needed to create partnerships; nonetheless, challenges exist. Aim This study aimed to gain insights into the experiences of families collaborating with staff. Method Semi-structured interviews were held with 30 family caregivers of nursing home residents with dementia. Findings Data reflected three themes, which shaped collaboration with staff from families’ perspective, ‘communication’, ‘trust and dependency’ and ‘involvement’. Discussion Good communication appeared to be a requisite condition for having trust in staff and quality of involvement in residents’ life. Good communication was described as having informal contact with staff, which enabled family and staff to build a personal connection. Consequently, this seemed to increase trust and satisfaction regarding involvement. Conclusion Findings suggest that increasing informal contact and building a personal connection should be a priority for staff in order to improve collaboration and to create partnerships with families.